Analisis Pengungkapan CSR Perbankan Syariah di Indonesia Berdasarkan Islamic Social Reporting Index - Junaidi Junaidi (Universitas Muhammadiyah Yogyakarta, Indonesia, 2015)
The aim of this study was to analyze the implementation of Corporate Social Responsibility (CSR) as measured using an ISR index throughout Sharia banks in Indonesia using content analysis method. This study specifically analyzes the theme of financing and investment, governance and civil society organizations because the theme is considered the most appropriate for the social responsibility disclosure based on Islamic principles and rules. ISR analysis performed with reference to the 2014 annual report published by each Islamic bank. The results showed that BMI, BSM and BNIS scored the highest 91% and lowest scores are BRIS scored 54%.